QUESTIONNAIRE FOR THE PATIENT'S HEALTH IN THE DENTAL ANAMNESIS - Dobrinka Damyanova (Peytchinski Publishing, 2021)
Purpose: The study aims to test the knowledge of a selected group of parents of child patients regarding the diagnosis, the health status of the children, and the choice of a medical institution in the Varna region. Material and methods: Respondents answered questions about knowledge concerning: general health, a change in general health, child's admission to hospital and whether it was ill during the last three years, whether a doctor is treating the patient for a general medical or systemic disease, pain that has occurred at the moment, and how parents choose a medical institution with modern dental services and others. For data analysis, we applied a test and mathematical model of SPSS v. 20. Results: Nine children (22.50%) of the surveyed participants are currently complaining of pain caused by a dental problem. Parents report two children with past dental illnesses. The main source of information about the services offered by the University Medical and Dental Center in the city of Varna is relatives and acquaintances who have used the center's services (40.00%), followed by the information published on the Internet (30.00%). Conclusions: The study improves the parents' knowledge, the choice of clinical and paraclinical methods in the anamnesis, diagnosis, methods and quality of treatment in childhood. The obtained results are also applied in the future planning of new clinical and treatment goals.